The Application of Technology to Increase Palm Sugar Production from Palmyra Sap (Borassus flabellifer L.) in Household Industries in Oirata Village, Southwest Maluku - Priska Pattiasina; Nelson Gaspersz; Marfin Lawalata (Unram Journal of Community Service, 2025)
Southwest Maluku, particularly Kisar Island, has abundant natural resources that can be optimally managed to address food shortages. Meeting food needs through local wisdom is an essential capital that must be strengthened by both the government and the community. One of the island’s local potentials is the koli tree (Borassus flabellifer L.), which grows widely in Oirata Village. Its sap can be processed into koli palm sugar, which is highly nutritious and economically valuable. Unlike other sugar sources, the koli tree grows naturally without cultivation and can be tapped at any time. However, its production has not yet been properly managed to meet market demand. Through the Community Partnership Program, we introduced appropriate technology in the form of palm sugar cooking equipment to improve both the quality and quantity of koli palm sugar. This innovation is expected to expand its market beyond Kisar Island. The program includes community socialization, training on equipment use, production assistance, and product packaging with proper labeling, aiming to empower the people of Oirata Village and enhance their local enterprises.